Strategizing em formas fluidas de socialidade: um estudo com tribos urbanas que atuam em Uberlândia - Giordani, Francine Câmara (2019)
This research proposes a dialogue between the sociological concept of urban tribes proposed by Michel Maffesoli to characterize social life, especially in the metropolises, and the concept of strategizing, central in the studies of strategy as a social practice. Both the concept of urban tribes and the perspective of strategy as a social practice emerged from proposals for the study of postmodern socialism or after modernism. The purpose of this research is to analyze how strategizing is practiced in fluid forms of sociality: the urban tribes. The research question is: how can the study of strategy as a social practice be used in the application of the concept of strategy in fluid forms of sociality? Regarding the methodological procedures, the qualitative approach of the material collected in the field research, elements of ethnomethodology and the case study method were used. As for the field research procedures, we used the technique of in loco observation of the tribes and of tribe interactions in online social networks, with registration in the field notebook and interviews with tribesmen. The results are presented in four stages: the tribes are located temporally and spatially; a brief history of the urban tribes surveyed is presented; the strategizing practices of the five urban tribes are analyzed from the characteristics identified by Maffesoli (1997, 2014a, 2014b, 2016): ambience, identity, aesthetics, ethics, sociality, transfiguration of the politician and homo eroticus / homo festivus; and, a section with the contributions of strategizing practices in fluid forms of sociality to the concept of strategizing. The results show the transience of strategic practice. Strategizing practices in urban tribes contribute to the study of strategy as a practice by showing various emerging and ephemeral strategic manifestations, dispersion and teleological absence in the quest for existence of the tribe, the role of ethics and aesthetics in everyday interactions, representation transient and unstable nature of multiple roles and their relation to the horizontality of relationships, the focus on practitioners who build organizational groupings, the transfiguration of the political in the tribes' interactions with the social and environmental environment, the pursuit of play and its role in the generation of emotions and tensions. Thus, by approaching strategy research as a practice of postmodern analysis assumptions, the dissertation offers an alternative for overcoming functionalist rationality in traditional strategy studies.